2019
DOI: 10.2215/cjn.07320619
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B, Triglyceride-Rich Lipoproteins, and Risk of Cardiovascular Events in Persons with CKD

Abstract: Background and objectives Triglyceride-rich lipoproteins may contribute to the high cardiovascular risk of patients with CKD. This study evaluated associations of apo-B and markers of triglyceride-rich lipoproteins with cardiovascular events in people with CKD.Design, setting, participants, & measurements Analyses were conducted in 9270 participants with CKD in the Study of Heart and Renal Protection (SHARP): 6245 not on dialysis (mean eGFR 26.5 ml/min per 1.73 m 2 ), and 3025 on dialysis when recruited. Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
0
33
1
2
Order By: Relevance
“…Body mass index (BMI) was determined as body weight (kg) divided by body height (m 2 ). Non-high-density lipoprotein cholesterol (non-HDL-C) was calculated as TC minus HDL-C, triglyceride-rich lipoprotein was calculated as non-HDL-C minus LDL-C as the previous study showed [23]. The value of atherogenic index of plasma was defined as the base 10 logarithm of the ratio of the concentration of TG to HDL-C, the lipoprotein combine index (LCI) was defined as the ratio of TC × TG × LDL-C to HDL-C [24].…”
Section: Calculation Of Parametersmentioning
confidence: 99%
“…Body mass index (BMI) was determined as body weight (kg) divided by body height (m 2 ). Non-high-density lipoprotein cholesterol (non-HDL-C) was calculated as TC minus HDL-C, triglyceride-rich lipoprotein was calculated as non-HDL-C minus LDL-C as the previous study showed [23]. The value of atherogenic index of plasma was defined as the base 10 logarithm of the ratio of the concentration of TG to HDL-C, the lipoprotein combine index (LCI) was defined as the ratio of TC × TG × LDL-C to HDL-C [24].…”
Section: Calculation Of Parametersmentioning
confidence: 99%
“…However, genetic mutations that lead to similar lipid profiles are not associated with the development of CKD ( Lanktree et al., 2018 ). Patients with CKD and dyslipidemia are at high risk of cardiovascular complications, and a recent post hoc analysis of the Study of Heart and Renal Protection (SHARP) trial data has shown that high triglycerides are independently associated with worse cardiovascular outcomes ( Lamprea-Montealegre et al., 2020 ). Our data suggest that the presence of CKD alone may generate this abnormal lipid profile, which, along with the accumulation of uremic endothelial toxins such as indoxyl sulfate, may provide insights into the close association between CKD and cardiovascular disease ( Lano et al., 2020 ; Provenzano et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not consider apolipoproteins B or A1 since many previous studies have reported on them and also a clear superiority of apolipoproteins over traditional lipids in their association with eGFR or CKD has not been suggested [ 10 ]. Recently, a TG/HDL-C ratio was comprised of the potential risk factors for atherosclerotic vascular events in CKD [ 15 ]. In agreement, in our study we noted a significant unadjusted association of a high TG/HDL-C ratio with manifested hypertension and the patients with a higher TG/HDL-C ratio had significantly higher blood pressure and arterial stiffening in comparison to the group of patients with a lower TG/HDL-C ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The TG to HDL-C (TG/HDL-C) ratio has been already included in the potential indices for an increased risk of atherosclerotic vascular events in CKD [ 15 ], although a few studies considered its role on the chronic renal disease until now.…”
Section: Introductionmentioning
confidence: 99%